Migration of juvenile and sub‐adult Chinese sturgeon Acipenser sinensis Gray, 1835 in the Yangtze River, China below the Gezhouba Dam. (24th September 2014) - Wang, C. Y.; Du, H.; Zhang, H.; Wu, J. M.; Liu, Z. G.; Wei, Q. W.
Summary Acoustic telemetry data and recapture information were collected to study the distribution and migration of sub‐adult and juvenile Chinese sturgeon Acipenser sinensis. From 2007 to 2012, 187 537 tagged cultured fish (4637 sub‐adults and 182 900 juveniles) were released at two sites on the Yangtze River. Subsequently, 482 fish were caught, comprising 198 cultured fish and 284 wild fish, mostly near sandbanks and sandbars with flat topography and slow water flow rates. Acoustic monitoring showed that a single sub‐adult fish migrated upstream to the spawning grounds just below the Gezhouba Dam, a distance of 157 km at an upstream ground speed of 0.40–1.40 km h−1 (mean, 0.70 km h−1). Nine acoustically monitored sub‐adults made a downstream migration of 45–1521 km at a ground speed of 0.08–3.80 km h−1. The ground migration speed of fish upstream to Wuhan (rkm 1678–1071) was significantly lower than that from Wuhan to the Yangtze estuary (rkm 1071–94). There was no significant difference in the ground migration speed between cultured and wild individuals. Knowledge of the movement and migration patterns of the stocked juvenile and sub‐adult Chinese sturgeon will help to locate areas of the downstream channel in the lower reaches of the Yangtze River critical to the sturgeon and to evaluate the potential impact of the Three Gorges Dam on their downstream migration.